2005
DOI: 10.1258/004947505774938710
|View full text |Cite
|
Sign up to set email alerts
|

Does maternity care improve pregnancy outcomes in women with previous complications? A study from Zimbabwe

Abstract: To determine the utilization of maternal health care services and pregnancy outcomes for women with a history of complications in previous pregnancy, we analysed the pregnancy records of multiparous women (parity > or =1) who booked and completed follow-up in Gutu district, Zimbabwe between January 1995 and June 1998. Women with previous uncomplicated pregnancies (n = 6140) were classified as low risk, whereas those with complications of previous pregnancy (n = 1077) were classified high risk. At enrolment, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
1
6
0
1
Order By: Relevance
“…Cross-sectional studies in Africa have reported recurrence risks of preeclampsia and hypertension, ranging from15.8% to 36% [13,16]. The estimated recurrence risk of preeclampsia in our prospective study falls within this range.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Cross-sectional studies in Africa have reported recurrence risks of preeclampsia and hypertension, ranging from15.8% to 36% [13,16]. The estimated recurrence risk of preeclampsia in our prospective study falls within this range.…”
Section: Discussionsupporting
confidence: 63%
“…Some studies in Africa have reported recurrence risks of hypertension [12,13]. However, these studies were based on cross-sectional data and had limited sample size.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recommended for pregnant women to visit antenatal care providers at least one time during the first trimester, twice during the second trimester, and five times during the third trimester [24]. While reasons for the overall overutilization of antenatal care have not been explored in the study, such behavior could be a result of pregnancy complications or anxiety in women classified as at high risk of such complications [25]. The concerning lack of the perceived value of antenatal care and its association with women's education, previously identified by [26] in a local study, remains to be an important and long-manifested barrier to the utilization of maternal health services in many low-income settings [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…En fait, le nombre de visites prénatales des femmes ayant une grossesse à risque dépasse cinq au Zimbabwe [28]. Cependant, dans d'autres études concernant le pronostic de la grossesse et de l'accouchement chez les femmes ayant comme facteur de risque l'âge avancé, le nombre moyen de visites prénatales chez celles-ci est de 5,1 alors qu'il est de 7,5 chez les femmes jeunes [29].…”
Section: Discussionunclassified